DNA methylation patterns of circadian and ultradian genes are altered in the peripheral blood of patients with hidradenitis suppurativa - Radhakrishna, Uppala; Ratnamala, Uppala; Jhala, Devendrasinh D.; Uppala, Lavanya V.; Vedangi, Aaren; Saiyed, Nazia; Shah, Sushma R.; Patel, Maulikkumar; Rawal, Rakesh M.; Mazza, Tommaso; Jemec, Gregor B. E.; Mazzoccoli, Gianluigi; et al. (Frontiers in Immunology, 2024)
BackgroundHidradenitis suppurativa (HS) is a chronic inflammatory skin condition that affects hair follicles in areas with apocrine sweat glands, such as the underarms, groin, and buttocks. The pathogenesis of HS is not fully understood, but considering the key role played by the biological clock in the control of immune/inflammatory processes the derangement of circadian and ultradian pathways could be hypothesized.MethodsWe analyzed genome-wide DNA methylation patterns in peripheral blood from 24 HS cases and 24 controls using the Infinium HumanMethylation450 BeadChip array (Illumina), followed by bioinformatics and statistical analyses.ResultsWe found that several circadian and ultradian genes were differentially methylated in HS patients, predominantly exhibiting hypomethylation. These genes were enriched in pathways such as MAPK and WNT cascades, acute phase response, cytokine release, inflammation, innate immune response, xenobiotic detoxification, and oxidative stress response.ConclusionAltered DNA methylation patterns of genes related to circadian and ultradian pathways could contribute to immune system derangement and inflammatory processes chronicization in addition to other comorbidities hallmarking HS onset and progression, at the same time representing possible druggable targets.